RESPON BERBAGAI VARIETAS PADI SAWAH (Oryza sativa L.) YANG DITANAM DENGAN PENDEKATAN TEKNIK BUDIDAYA JAJAR LEGOWO DAN SISTEM TEGEL - Haryanto Sitinjak; Idwar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This Researh was aimed to determine growth and the best paddy rice variety with cultivation approacment and of jajar legowo and tegel system. The research was conducted at the farmer’s wet rice field in Sikek village, Rimba Melintang subdistrict, Rokan Hilir regency and start from Juni to October 2014. This research utilized Randomized Blok Design (RBD) factorial, The first factor was paddy rice, consist of 4 varieties: Inpara 4, Inpari 30, IR 64 and Situ Bagendit. The second factor was cultivation approachment, consist of jajar legowo and tegel system. The treatment consist of 8 combination with 3 replication so obtained 24 plot units. Parameters observed were the plant height, number of total tillers, number of productive tillers, age out of tassel, long of tassel, harvest, amount of grain per tassel, amount of dry grain per plot, percentage of unhusked grain per plot and weight of 1000 grains. Data were analyzed using Analysis of Variance (ANOVA). The data were further tested by Duncan new multiple range test (DNMRT) at the level 5%. The research result showed that planting paddy rice of Inpari 30 variety with approachment of jajar legowo cultivation technique 4:1 indicated better yield than tegel system. Keywords: Paddy rice, Jajar legowo 4:1, tegel system